Association of Epilepsy in Children Experiencing Febrile Seizure: Findings from National Institute of Neuroscience, Bangladesh (The Journal of Ad-din Women's Medical College, 2023)
Background: Febrile seizure-(FS) remains the commonest benign convulsive childhood event. Prolonged-FS may have long-term consequences, including increased risk of subsequent-epilepsy.Objective: To assess if there is any association among epilepsy and epilepsy syndrome with FS.Methodology: This cross-sectional study was conducted in Epilepsy Clinic, National Institute of Neurosciences, Bangladesh, from January-June, 2021 involving one hundred 1-18 years-old-children diagnosed as epilepsy without secondary causes (intracranial space occupying lesion, head-trauma, CNS-infection, stroke). Patients were clinically evaluated thoroughly and were divided into two groups (Gp): Gp-A having a history of (H/O) FS and Gp-B, without FS. Demographically, clinical profile and electrophysiological-parameters were compared between the two groups for association with H/O FS. Pre-checked/cleaned-data were analyzed using SPSS.V.22.0 for proportional differences, taken p